KEBIJAKAN PELAYANAN KESEHATAN REPRODUKSI REMAJA - Joyce S.H. Djaelani (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
Indonesian adolescents are 37 per cent of the total of population of this country. The large quantity, however, is comparatively unequal to the right of reproduction health service they receive. They are often seen in the position as an